FORMATION OF LOCAL SELF-GOVERNMENT IN POLAND IN THE CONTEXT OF ADMINISTRATIVE-TERRITORIAL REFORM: ESTIMATION OF EXPERTS - Бровко, О. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article deals with the formation of local self-government in Poland during gmina and administrative-territorial reform. The basic stages of reforms and the most meaningful changes in local self-government of Poland, that took place because of reformation, are analysed. Moreover, the author answers the question of how the entering of Poland into UE influenced the process of forming local self-government. Basic problems, that were not overcame as a result of reform and new problems that arose up as a result of the realization of reform are determined. The research is undertaken on the basis of deep interviews with the leading Polish experts in the field of local self-government.